Solar Tracker: A Review - Taheem, Anubhav; Sachdeva, Anish; Sharma, Vishal S (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 6 No 3&4 (2019): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
A solar tracker is a traditional term used to describe devices that coordinate or align different payloads with the sun. The aim of the automatic sun tracking system is to retain the photovoltaic solar panel perpendicular to the sun throughout the year to make it more efficient. A solar power transforms sunlight into electricity. This automated sun tracking system helps generate power by automatically tuning the device for optimum sunlight. Through reducing light intensity, this system will automatically change its direction to reach maximum amount of light. Light intensity is the big problem with solar power generation. To produce the maximum energy, a solar panel must be upright and face-to-face with the light source. Because the sun moves all through the day as well as throughout the year, in order to produce as much energy as possible, a solar panel must be able to follow the sun’s movement. The approach is to use a light source tracking system to preserve the panel’s orthogonal location. Several tracking systems models exist, including passive and active systems with one or two freedom axes. Solar trackers are used with different sensors to dramatically increase the electrical power of the photovoltaic panel.Photovoltaic systems are rapidly becoming a fresh source of energy by capturing the solar radiation. Optimizing its power output is desirable in order to increase its efficiency. The panels must be aligned with the sun in order to optimize the power output of solar panels. It has been estimated that energy derived from solar panels can be expanded by 20 to 30% by using a tracking system instead of a stationary array. Over time, different approaches have been developed. Astronomical or time-based systems are the most popular, and then optical approaches are used to align the PV components with different image sensor types. How to cite this article: Taheem A, Sachdeva A, Sharma VS. Solar Tracker: A Review. J Adv Res Alt Energ Env Eco 2019; 6(3&4): 34-50. DOI: https://doi.org/10.24321/2455.3093.201905